Analisis Pengaruh Gaya Kepemimpinan, Disiplin Kerja, dan Budaya Organisasi terhadap Kinerja Karyawan pada Machinery dan Spare Part Industries - Ridma Meltareza; Prima Arti (Universitas Informatika dan Bisnis Indonesia, 2023)
This research aims to understand the impact of leadership style, work discipline, organizational culture, and employee performance at CV. Indo Karya Teknik Pameungpeuk-Bandung, as well as to analyze the influence of leadership style, work discipline, and organizational culture on employee performance in the company. The theory that will be used in this research is organizational communication theory. The data analysis will utilize regression and correlation analysis. The statistical calculations will be done using multiple regression. The research method employed in this study is a quantitative approach with a descriptive and verificative approach. The population of this study consists of a total of 69 employees at CV. Indo Karya Teknik Pameungpeuk-Bandung. Data collection will be conducted through questionnaire distribution. The results of the analysis indicate that leadership style, work discipline, and organizational culture have a significant impact on employee performance. This is evidenced by the coefficient of determination, which shows that the influence of leadership style, work discipline, and organizational culture on employee performance is 62.1%.